Nitric oxide, carbonyl protein, lipid peroxidation and correlation between antioxidant vitamins in different categories of pulmonary and extra pulmonary tuberculosis - Dalvi, Shubhangi Mahesh; Patil, Vinayak Wamanrao; Ramraje, Nagsen Nirgun; Phadtare, Jaising Marutrao; Gujarathi, Sarita Uday (The Malaysian journal of medical sciences, 2013)
Lipid peroxidation, nitric oxide, carbonyl protein, causing production of reactive oxygen and reactive nitrogen intermediates that lead to oxidative, nitrosative stress. The stress is found to cause deterioration in the cellular function, mutagenesis, and DNA damage. The oxidative stress is correlated with the antioxidant vitamins status. Newly diagnosed cultured positive sputum pulmonary category I, II, III (n = 100 each), extra pulmonary category I (n = 35) before and after directly observed short course treatment of six months vitamins, by HPLC. Oxidative parameter levels were significantly increased, and activities of vitamins were found to be significantly decreased in subjects of all categories of pulmonary and extra pulmonary tuberculosis. Positive correlations between nitric oxide, carbonyl protein, and lipid peroxidation were seen among them. Negative correlations between nitric oxide, carbonyl protein, lipid peroxidation with vitamin E, C, A were seen in tuberculosis (two sided P < 0.01). Increase oxidative stress and nitrosative stress, leading to protein carbonyl formation in tuberculosis. The increased protein carbonyl, hampers many important functions of proteins. The changes were reversed after six months of antitubercular treatment in patients with good recovery but increase stress was not completely reversed.